Dampak Ketimpangan Pendapatan dan Tingkat Pengangguran Terbuka Terhadap Kriminalitas di Wilayah Sumatera Utara - Alexa Angelica Nababan; Joko Suharianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of income inequality and the open unemployment rate (TPT) on crime rates in North Sumatra Province. The data used in this study are secondary data over a certain period, analyzed using a linear regression method. The results show that, partially, income inequality does not have a significant effect on crime rates. This indicates that income inequality is not the main factor influencing crime in North Sumatra. Meanwhile, the open unemployment rate has a significant effect on crime with a negative relationship, meaning that an increase in unemployment is associated with a decrease in crime rates. Simultaneously, both variables have a significant effect on crime rates. However, the model's ability to explain variations in crime is relatively limited, suggesting that other factors outside the model also influence crime rates.This study is expected to provide insights for policymakers in formulating strategies to reduce crime, particularly through economic and social approaches.